Design and Performance Evaluation of an Energy Efficient Manure Shredder Pulverizer for Organic Fertilizer Production - Damayanti, Annisa Maulidia; Amalia, Zakiyah; Permatasari, Dinda Ayu; Wicaksono, Rendi Pambudi; Hasanah, Qonitatul; Puspitasari, Etik (Universitas Muhammadiyah Surakarta, 2025)
The growing demand for organic fertilizer calls for innovations in manure processing technology to enhance production efficiency and product quality. This study presents the design, fabrication, and performance evaluation of a prototype manure shredder–pulverizer that integrates dual shredding and pulverizing functions to accelerate the composting process and produce uniform particle sizes. The machine is powered by a 6.5 HP gasoline engine and tested using fresh goat manure with an average moisture content of approximately 70%. Performance evaluation focused on processing capacity, particle size distribution, specific energy consumption, and output homogeneity. The prototype achieved an average processing capacity of 96.4 kg/h, with more than 82.5% of the processed material passing through a 4 mm sieve and a dominant fraction of 2–4 mm (54.0%), which is ideal for composting. The specific energy consumption averaged 0.050 kWh/kg, lower than reported values for comparable small-scale biomass shredders. The homogeneity index consistently rated as Good, indicating stable particle size distribution across repeated trials. These findings demonstrate that the developed prototype provides a practical, energy-efficient, and low-cost solution for small-scale organic fertilizer production, supporting sustainable agricultural practices and reducing reliance on chemical fertilizers.